(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This is a review of an intense and complex work, in which the author creates the metaphorical concept of seductive realism, with the aim of revisiting the appropriation of the word theater that branches out to the real-fiction binarism associated with the Aristotelian tradition. The proposal makes us think about the education of the body in and for art, Ribeiro instigates to think that acting is not interpreting reality, but experiencing it through an intuitive body, which interferes and is interfered by the social, political, economic and social environment. culturally, affectively, therefore seductive, revolutionary, transgressive. In this, it challenges what is understood and what is taught about theatrical art, when it proposes to break with the screens of reality and representation that condition us. invests in a multiple, untimely Artaudian body, which unfolds throughout the text in other concepts, machinic, biopolitical, anthropophagic, aesthetically emancipated bodies.